2002
DOI: 10.1046/j.1440-1819.2002.01038.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Ser9Gly polymorphism in the dopamine D3 receptor gene with tardive dyskinesia in Korean schizophrenics

Abstract: Tardive dyskinesia (TD) is usually regarded as one of the most serious side-effects of the longterm usage of neuroleptics due to its high prevalence and potentially irreversible nature. Previously, several genetic polymorphisms were investigated for an association with TD in various ethnic populations. Among them, the Ser9Gly variant in the MscI restriction site of the dopamine D3 receptor gene was reported to be associated with TD. We have investigated the association of Ser9Gly polymorphism of the dopamine D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Ten studies reported experiences of typical antipsychotic use in their study populations, while three studies did not specify types of antipsychotic. Four studies had genotype counts of 2 or smaller in the cross-classification of TD by genotype cell [Steen et al, 1997;Liao et al, 2001;Woo et al, 2002;Zhang et al, 2003]. In the sensitivity analysis, the meta-analytic results were very similar across the different approaches to smoothing or continuity correction [Sweeting et al, 2004].…”
Section: Description Of Studiesmentioning
confidence: 91%
“…Ten studies reported experiences of typical antipsychotic use in their study populations, while three studies did not specify types of antipsychotic. Four studies had genotype counts of 2 or smaller in the cross-classification of TD by genotype cell [Steen et al, 1997;Liao et al, 2001;Woo et al, 2002;Zhang et al, 2003]. In the sensitivity analysis, the meta-analytic results were very similar across the different approaches to smoothing or continuity correction [Sweeting et al, 2004].…”
Section: Description Of Studiesmentioning
confidence: 91%
“…87,176,289 Polymorphisms in D3 receptors were first reported to contribute to drug-induced TD by Steen et al 230 and by Segman et al 231 In both studies, individuals with one or two copies of the Gly allele of a D 3 Ser9Gly polymorphism were more likely to develop TD with antipsychotic treatment. Several subsequent studies failed to replicate this finding, 204,232-234 but a combined study of 780 patients of different ethnic background, 235 and further reports of association in the United States, Chinese and Korean patients 221,236,237 confirm the validity and strength of this finding. The Gly variant is reportedly associated with significantly higher dopamine activity, which in turn could explain the association with movement disorders.…”
Section: Prediction Of Side Effectsmentioning
confidence: 93%
“…In addition, a number of studies suggest a relationship to tardive dyskinesia, sex, and the age of onset. Especially the relationship to tardive dyskinesia was shown nicely in a number of studies (Steen et al, 1997;Basile et al, 1999;Segman et al, 1999;Woo et al, 2002). Since there have been also negative findings (Rietschel et al, 2000) it is important to note that in a recent study investigating a large pooled sample of 780 patients drawn from six research centers, a significant association of the DRD3 genotype with tardive dyskinesia was described (Lerer et al, 2002).…”
Section: Introductionmentioning
confidence: 89%